THE ADOPTION OF E-WALLET BY GENERATION Z IN KUALA LUMPUR, MALAYSIA - Mustafa , Muhammad Anas; Singh , Jugindar Singh Kartar; Ahmad , Noraini Binti (Electronic Journal of Business and Management, 2022)
Electronic payments and e-wallets are emerging globally, but growth remains slow in Malaysia. As Generation Z enters the workforce, they represent the largest consumer cohort for e-payments. This study examines the determinants of Generation Z's intention to use e-wallets in Kuala Lumpur. Using a deductive approach and cross-sectional design, data was collected from 92 respondents. The study tested the influence of trust, ease of use, and perceived security. Findings revealed that trust and perceived security are significant predictors of intention to use. Interestingly, perceived ease of use was not a significant predictor, likely because Generation Z is already highly familiar with smart devices. The results help marketers and web-retailers develop strategies to improve e-wallet adoption by focusing on security and trust.